A new potential of scalable method for the production of calcium carbonate by Bacillus sphaericus in batch fermentation - Adzami, Nuraiffa Syazwi; Ghazali, Miskiah Fadzilah; Ramli, Amira Hidayati; Tajarudin, Husnul Azan; Daud, Zawawi (International Journal of Integrated Engineering, 2019)
Bacteria is believed to induce calcium carbonate precipitation as it meets the concept of bioconcrete. Bacillus sphaericus was found to produce enzyme urease capable to hydrolyse urea, thus generate carbonate ions.  The excess presence of calcium ions in the system will precipitate calcium carbonate.  Therefore, the used of bioreactor to produce calcium carbonate can meet the demand for calcium carbonate as it can be produced in large-scale production thus maximize the production of calcium carbonate. The aim of this paper conducted by using 2.5 L bioreactor was to investigate the precipitation of CaCO3 and to optimize the production of H2CO3 by using different parameters such as agitation and aeration. As this is a preliminary study, the artificial urea is used as the carbon source of the Bacillus sphericus. The determination of the kinetics of CaCO3 precipitation in the 2.5 L batch bioreactor such as specific growth rate (µ) and doubling time (Td) were studied after fermentations were stopped. The composition of calcium carbonate characteristic from the fermentation of Bacillus Sphaericus in 2.5 L bioreactor of pH 8.0 and 30 °C were proved by X-Ray Diffraction. The highest specific growth rate (0.141 h-1) was determined from 50 rpm with 2.0 vvm aeration rate.  The optimum parameters condition to produce bicarbonate ions and calcium carbonate was at 50 rpm with 2.0 vvm aeration rate.